Tumor treating fields combined with ionizing radiation inhibit the malignant phenotype of lung cancer brain metastasis cells by suppressing DNA damage repair pathways - Guilong Tanzhu; Haiqin Peng; Liu Chen; Gang Xiao; Jiaoyang Ning; Ling Chen; Rongrong Zhou (Brain Stimulation)
Background: Brain metastasis (BrM) is a common complication of advanced tumors with poor prognosis. Although radiotherapy remains a key treatment for BrM, it is plagued by issues such as radiation-induced brain necrosis, neurocognitive impairment, and progress post-treatment. Tumor Treating Fields (TTFields) therapy employs medium frequency (100∼300 kHz) and low intensity (1∼3 v/cm) alternating electric fields to inhibit tumors. We explored the effects and mechanisms of TTFields combined with ionizing radiation (IR) on the malignant phenotype of lung cancer brain metastasis (LCBM) cells, with the aim of advancing the clinical adoption of TTFields. Methods: LCBM cells H1915, PC9-Brm and primary cells were used. The experiments included four groups: Control, 6 Gy, TTFields, and 6 Gy + TTFields group. Cell viability and the number of EDU or Ki67-positive cells, ability of migration and colony formation were assessed; Cell morphology was observed by H&E staining; Bulk transcriptome revealed the potential mechanisms, with the protein levels of differentially expressed genes (DEGs) verified through immunofluorescence assay. DNA damage repair pathways were validated by Western Blot. Additionally, ROS levels, and HO-1 expression were evaluated. Results: The combination of 150 kHz, 2∼2.5 v/cm TTFields and 6 Gy IR effectively suppressed the viability and the number of EDU-positive and Ki67-positive LCBM cells. Following TTFields and IR, the tumor cells exhibited altered morphology and reduced clonogenic and migratory capacities. RNA-seq revealed associations between TTFields combined with IR and various biological processes and mechanisms, including redox reactions (primarily related to mitochondria), DNA replication, transition metal ion transmembrane transport, and heme metabolism. Furthermore, TTFields combined with IR enhanced γH2AX and 53BP1 levels. Increased ROS and HO-1 expression were observed post-treatment. Similarly, LCBM primary cells exhibited decreased Ki67-positive cells along with increased γH2AX and 53BP1 foci following TTFields and IR. TTFields combined with IR exhibited significant suppression on homologous recombination (HR) markers (p-ATM, RAD51), non-homologous end joining (NHEJ) components (DNA-PKcs, KU70, KU80), and microhomology-mediated end joining (MMEJ) effectors (PARP1, p95-NBS1) versus RT alone. Conclusions: TTFields combined with IR effectively inhibits LCBM cells. Mechanistically, this combined treatment enhanced DNA damage, suppressed DNA damage repair, and elevates ROS levels.